Sympathetic nerve function status and their relationships with ovarian hormones in healthy young women - Naher, Latifa Afrin Dill; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2016)
Background: Alteration of sympathetic nerve activity during different phases of menstrual cycle in healthy young women, has been found related with phasic fluctuation of ovarian hormones. Objective: To observe relation of sympathetic nerve function status with estrogen and progesterone during follicular and luteal phases of menstrual cycle in healthy young women. Methods: This cross sectional study was carried out in the Department of physiology of BSMMU, Dhaka from 1st January to 31st December 2007. Thirty apparently healthy unmarried women with age 20 to 30 years were selected. Sympathetic nerve function was evaluated by 2 reflex tests, orthostatic test and sustained handgrip, during the three phases of menstrual cycle. Serum estrogen and progesterone were measured during follicular and luteal phases. Data were analyzed by One way ANOVA, an unpaired t test and Pearsons correlation coefficient where applicable. Results: There were no significant significant differences among sympathetic nerve function parameters during three phases of menstrual cycle. Serum estrogen and progesterone showed non significant (p>0.05) relationship with sympathetic nerve function parameters. Conclusion: From this study it may be concluded that sympathetic nerve activity remains unaltered despite fluctuation of ovarian hormones in different phases of menstrual cycle in healthy young women. Bangladesh Soc Physiol. 2016, June; 11(1): 13-17